if(a+b+c=0) than

Algebra

if(a+b+c=0) than

Postby Guest » Sat Mar 09, 2019 11:14 am

hello
if a+b+c=0 prove (a5+b5+c5)/5=abc∗((a2+b2+c2)/2)=((a2+b2+c2)/2)∗((a3+b3+c3)/3)

I can prove it abc∗((abc∗((a2+b2+c2)/2)=((a2+b2+c2)/2)∗((a3+b3+c3)/3) very easy
but i don't know what to do whit (a5+b5+c5)/5 .

I can do this, too: ((a2+b2+c2)/2)∗((a3+b3+c3)/3)=...=a5+b5+c5−abc(ab+ac+bc)

I will be very thankfull if someone help :D
Guest
 

Return to Algebra



Who is online

Users browsing this forum: No registered users and 3 guests